F-responses: a study of frequency, shape and amplitude characteristics in healthy control subjects. Issue 11 (November 1985) - Peioglou-Harmoussi, S; Fawcett, P R; Howel, D; Barwick, D D
Abstract : Characteristics of the surface recorded F-response, including frequency, occurrence of identical responses, shape and amplitude have been investigated in the ulnar nerve of control subjects. During a train of 200 stimuli, F-response frequency varied between 50% and 93% in different subjects with a mean of 79%. The vast majority of responses (96.6%) occurred only once; of those responses which repeated, 89.5% occurred between 2-5 times, 9% between 6-10 times and only 1.5% 11 or more times. F-response shape was variable, the majority containing two or more negative peaks. F-response amplitudes tended to be a relatively small proportion of the compound M-response, with median F%M values ranging from 0.8% to 4%. The data suggest that a large proportion of surface recorded F-responses following supramaximal stimulation are composed of recurrent discharges derived from more than one motor unit.